Characteristics of the relative clause in Korean and the problems second language learners experience in acquiring the relative clause - Shin, Kyu-Suk (Curtin University, 2003)
The purpose of this study is to investigate three pertinent aspects of the relative clause in Korean: the form-function of the relative clause, the processing of the head-final relative clause and the acquisition of relative clauses as a second language. Based on universal typology, this study proposes that the linguistic category of the descriptive verb lies between the attributive adjective and the verb. With this identification, the study claims that the modifying ending -(u)n has the prototypical semantic function of the perfective aspect. The perfective aspect is, however, interpreted differently according to the verb types and this provides a solution to the form-function distinction: when the descriptive verb is suffixed by -(u)n, the attributive adjective expresses a permanent state; with the processive verb the relative clause denotes the completion of action or process. The analysis of the linear ordering of elements in the verb phrase reveals that grammatical morphemes are related in the strict grammatical rules, which progressively build up conceptualisation. Contrary to the views presented in previous studies, this study argues that incremental and left-to-right processing, the relative clause has semantic constraints on the head noun. The overall order of difficulty in the acquisition of relative clauses determined by a completion task, a combination task and a grammaticality judgment 'Oh OP>IO>SU>DO>GE, which does not accord with the Noun Phrase Hierarchy (NPAH).The study finds that markedness theory and configurational analysis are also unable to explain the order exhibited in this study due to the head-final at characteristics of the relative clause. The processing ease is the main contributing factor for learners successfully performing the tasks by utilizing the mental lexicon, SOV canonical word order, case particles and temporal adverbs in sentence initial position. The study also evaluates the effectiveness of instruction and the merits of pedagogical grammar. Incorporating findings from the present study, some suggestions are made for the development of a pedagogical grammar for the relative clause in Korean.